Utilizing Internet of Thing for Construction Waste Management in Pakistan - Muhammad Waheed; Mutahir Abbas; Shahzada Hassan Arif (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Construction waste is a significant environmental challenge in Pakistan, with the construction industry being a major contributor to waste generation. Efficient waste management practices are crucial to mitigate the negative impacts of construction waste on the environment and public health. The Internet of Things (IoT) has emerged as a promising technology that can revolutionize waste management practices in the construction industry by providing real-time monitoring, predictive analytics, and optimization of resources. This paper presents an overview of the utilization of IoT in construction waste management in Pakistan, highlighting the potential benefits, challenges, and future prospects of implementing IoT solutions in this context.